Comparison between body composition parameters and response to neoadjuvant chemotherapy by using pre-treatment PET CT in locally advanced breast cancer. (2020) - Kizildag Yirgin, Inci; Has, Duygu; Arslan, Gozde; Aydin, Esra Cureoglu; Sari, Murat; Onder, Semen; Yasemin, Sanli; Cabioglu, Neslihan; Karanlik, Hasan; Tukenmez, Mustafa; Dursun, Memduh; Muslumanoglu, Mahmut; et al.
Highlights: Weight and the BMI are inadequate proxies for adiposity that do not distinguish between muscle and adipose tissue or different specific deposits of adipose tissue (visceral and subcutaneous), which have different physiological effects. Patients with the same BMI are likely to have different anatomical distribution of adipose and muscle tissue. To our knowledge, only few studies have investigated the association between fat and muscle tissue distribution of the body, and response to neoadjuvant chemotherapy. Abstract: Purpose: To compare the adipose and muscle tissue areas in patients who responded differently to neoadjuvant chemotherapy. Methods: One hundred and eighty six patients diagnosed with breast cancer who underwent neoadjuvant chemotherapy between January 2015- October 2019 and were operated after the treatment were retrospectively included in the study. Pathological results were divided into five groups using the Miller-Payne grading systems. Grade 1 indicating no significant reduction in malignant cells; Grade 2: a minor loss of malignant cells (≤ 30 %); Grade 3: reduction in malignant cells between 30 % and 90 %; Grade 4: disappearance of malignant cells >90 %; Grade 5: no malignant cells identifiable. Pre-treatment PET CT scans were evaluated, and calculation of body composition parameters were performed on a single axial section passing through the L3 vertebrae. Spearman's correlation test was used to analyze the correlation between SAT, VAT, MT parameters and pathological responses. Results: There was no strong correlation between the 5 groups separated according to neoadjuvant chemotherapy treatment response and tissue distributions. However, that there was a very low correlation found between superficial adipose tissue and pathological response (r=, 156). Conclusion: In conclusion, our results have provided a very low correlation between SAT and more than 30 % response. More research is required to evaluate the role of the body fat and muscle parameters in response to neoadjuvant chemotherapy in larger patient populations.